On the forecastability of Asean-5 stock markets returns using time series models - Venus, Khim-Sen Liew; Lim, Kian−Ping; Choong, Chee-Keong (University Library of Munich, Germany., 2003)
This study examines the forecastability of ASEAN-5 stock market returns using linear and non-linear time series models. Time series models with GARCH errors are also considered. Based on formal econometrics tests, this study shows that the behaviour of these returns do not follow random walk movement. Results of this study also reveal that all the estimated time series models, both linear and non-linear, have smaller out-of-sample forecast errors than the random walk model. These two findings robustly indicate that returns of ASEAN-5 stock markets do not follow random walk movement and are forecastable. Thus, this study can be taken as providing justification for the work of technical analysts.